ESCALATION AND DE-ESCALATION OF WAR OBJECTIVES: THE ANALYSIS OF ASYMMETRIC WAR IN LEBANON (2006) - Indra Alverdian (President University, 2016)
This article tries to enrich the conceptual debate and discussions among international relations and strategic studies scholars regarding explanations of weak actor‟s victories against strong actors in military conflicts. For longtime strategic studies scholars have tried to find the most relevant and valid explanations on the reasoning on how a weak actor can achieve victory in asymmetric conflict despite overwhelming inferiority in terms of power. Previous strategic studies scholars have proposed competing hypothesis ranging from regime type, balance of interests to the types of strategic interaction between the two actors. In this essay, the author would like to underline the significance of fog of war or uncertainty as a significant contributing factor during strategic interactions at tactical-operational towards shaping either a favorable or vice-versa unfavorable war conditions for the weak actor to modify pre-war political objectives of the asymmetric conflict. In this analysis, the 2006 Lebanon War is taken as a case study of the asymmetric conflict between the strong and weak actor. The result strengthened the notion that there is no single variable but a multitude of variable which explains asymmetric conflict outcomes.